THE EFFECT OF TOMATO JUICE (SOLANIUM LYCOPERSICUM) ON BLOOD PRESSURE STABILIZATION IN HYPERTENSION PATIENTS IN YANTI CLINIC PERCUT SEI TUAN DISTRICT DELI SERDANG IN 2021 - Yusridawati Yusridawati (Science Midwifery, 2022)
Hypertension is a global health problem resulting in an increase in morbidity and mortality as well as the burden of health costs, including in Indonesia. Based on data from the Yanti Clinic for 5 months from October 2020 - February 2021, there were 57 hypertensive patients, of which 23 were male and 34 were female, aged over 25 years. The purpose of this study was to determine the effect of giving tomato juice (solanium lycopersicum) on blood pressure stabilization in patients with hypertension at the Yanti Clinic in 2021. The type of research is Quasi Experiment (Quasi Experiment) with one group pre and posttest design, the population of all patients with hypertension is 20 people. The sampling technique was purposive sampling with the inclusion criteria not taking hypertension drugs with a sample of 20 people, the instrument of this study used an observation sheet. Data analysis was carried out by using paired t-test. The results of the study before giving Tomato Juice (Solanium Lycopersicum) in patients with hypertension The majority of systolic was 160 mmHg, diastolic was 100 mmHg. After being given tomato juice, the majority of systolic was 130 mmHg, diastolic was 90 mmHg. The results of the paired t-test with a p value of 0.000 (< 0.005). showed the effect of Tomato Juice (Solanium Lycopersicum) on Blood Pressure Stabilization in Hypertensive Patients at Yanti Clinic. Based on the results of this study, it can be concluded that there is an effect of tomato juice (Solanium lycopersicum) on blood pressure stabilization in patients with hypertension at the Yanti Clinic in 2021. It is hoped that health workers will recommend using nonpharmacological methods (tomato juice) to lower blood pressure in hypertensive patients.